An Evaluation of the Mutual Aid Facilitation Sessions Pilot Program, "You do the MAFS". Issue 2 (2nd April 2016) - Aslan, Laura; Parkman, Thomas James; Skagerlind, Nina
ABSTRACT: Although recovery has gained considerable momentum in recent years, pathways into recovery programs are less understood. "You do the MAFS" is a 6-session, peer-led group that educates service users about abstinence-based recovery and provides a gateway into mutual aid. Through a mixed methodological approach, this study found that attendance at "You do the MAFS" improved participant health and social functioning, increased mutual aid attendance and reduced substance use. An intervention such as this would be a useful addition to the substance misuse treatment sector as provision to make links to and increase support for those in recovery.